The Overview of Bullying Behavior in Adolescents - Purba, Novia Sri Parindu; Septiyan, Septiyan (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Although bullying has been recognized as a serious problem, bullying cases are still very common, especially among adolescents. The purpose of this study is to look at the description of bullying behavior among adolescents. This research uses a quantitative descriptive approach. The participants of this study were adolescents from high school/vocational and university levels with a total of 250 participants. The participants were selected using a purposive sampling technique. The instrument used in this study was the Bullying Scale for Actual Use. A total of 17% of adolescents experienced little bullying, 65% experienced quite a lot of bullying, and 18% experienced a lot of bullying. The most common types of bullying experienced by adolescents were verbal bullying (49%), emotional/relational bullying (21%), physical bullying (14%) and cyberbullying (1.4%). 23% of the participants had sought help, while 77% of the participants had never sought help. This study shows that most participants who have experienced bullying choose not to seek help because they feel that no one can help them.Bullying sudah diakui sebagai masalah yang serius, dan masih sangat sering terjadi terutama di kalangan remaja. Tujuan dari penelitian ini adalah untuk melihat gambaran perilaku bullying pada kalangan remaja. Penelitian ini menggunakan pendekatan deskriptif kuantitatif. Partisipan penelitian ini adalah remaja yang berasal dari jenjang SMA/SMK dan Universitas dengan total partisipan sebesar 250. Partisipan dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah Bullying Scale for Actual Use. Analisis data menggunakan SPSS versi 25. Sebanyak 17% remaja mengalami sedikit bullying, 65% mengalami cukup banyak bullying, dan 18% mengalami banyak bullying. Jenis bullying terbanyak yang dialami remaja adalah bullying verbal (49%), bullying emosional/relasional (21%), bullying fisik (14%) dan cyberbullying (1,4%). Terdapat 23% partisipan pernah mencari bantuan, sedangkan 77% partisipan lainnya tidak pernah mencari bantuan. Penelitian ini menunjukkan kebanyakan partisipan yang pernah mengalami bullying memilih tidak mencari bantuan karena merasa tidak ada yang dapat membantu mereka.